Towards a low carbon economy in the Amazon:: the role of land-use policies (Sustainability in Debate, 2011)
Climate change, rising oil prices and the global financial crisis has put sustainability and‘green growth’ of the economy on the political agenda. While the transition towards a “low carbon”economy in developed countries like in the European Union should mainly be found in renewableenergy production, developing countries like Brazil face with high land use emissions which willfurther rise in the coming decades without proper policy instruments. Deforestation and cattleproduction are the main sources of land use emissions in Brazil and we expect that these emissionswill further rise with liberalisation of agricultural trade. A transition towards a “low carbon” economyin Brazil thus calls for appropriate, and effective land-use policies. Agricultural intensification onone hand can meet the world demand for soy and beef. For example we calculate that increasingthe meat content of cattle can reduce emissions from deforestation up to 30%, but intensificationmay also accelerate further deforestation of Cerrado and Amazon forests. In order to avoid suchadditional deforestation, large areas of degraded lands have to be taken back into production,which requires large agricultural investments. In addition, (new) economic instruments, monitoring,law enforcement and appropriate conservation policies are also needed to halt further deforestationand biodiversity loss. The recently amended change of the Forest Code policy, for example, isexpected to accelerate deforestation further, thus making more difficult to reach mitigation targetsfor the Brazilian State.